Virtual Reality Tennis Training: Performance Gains Derived from User Characteristics - Andel, Ross; McMahan, Timothy; Parsons, Thomas D; Hort, Jakub (Cyberpsychology, behavior and social networking, 2024)
There is growing interest in virtual reality (VR) training among competitive athletes and casual sports players alike as a tool to supplement real-life play within a highly controlled, intellectually stimulating environment. We examined data from a commercially available, recently released VR software for tennis for changes in and correlates of performance. Two most frequently used tasks were evaluated-Baseline Center and Quick Volley, which include Efficiency (both), Concentration (both), and Reaction Time (Quick Volley only) subtasks. In all, 1,124 (Baseline Center) and 745 (Quick Volley) users met inclusion criteria (completed more than four trials; active sometime between November 2022 and July 2023). We found that most users were male adults and were about evenly split between advanced/pro users and intermediate/beginner users. Two or three trajectories emerged across the subtasks. Performance gains were most pronounced on movement efficiency, especially early on. Adult users generally exhibited more improvement than junior users. Additionally, women and right-handed users improved more on Baseline Center subtasks, and advanced/pro users did better than intermediate/beginner users on Quick Volley subtasks. We discuss that, despite strong performance gains within VR environment, VR training may still reflect in better real-world performance, may increase confidence and accuracy of relevant movement, lower risk of injury, and present a welcome diversion from a potential monotony of performing sport-related tasks in purely real-world settings. Future research should explore the extent to which VR training transfers to real-world performance.
Keywords: Tennis; virtuální realita; mladý dospělý; Adult; Young Adult; Adolescent; virtual reality; mladiství; sportovní výkon; ženské pohlaví; Virtual Reality; lidé; Psychomotor Performance; tennis; Athletic Performance; mužské pohlaví; dospělí; Humans; athletic training; tenis; psychomotorický výkon; Female; Male